Differential ratings of perceived match and training exertion in girls` soccer - Wright, M. D.; Songane, F.; Emmonds, S.; Chesterton, P.; Weston, M.; McLaren, S. J. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To understand the validity of differential ratings of perceived exertion (dRPE) as a measure of girls` training and match internal loads. Methods: Using the centiMax scale (CR100), session dRPE for breathlessness (sRPE-B) and leg muscle exertion (sRPE-L) were collected across a season of training (soccer, resistance, and fitness) and matches from 33 players (15 [1] y). Differences and associations between dRPE were examined using mixed and general linear models. The authors` minimal practical important difference was 8 arbitrary units (AU). Results: Mean (AU [SD] ~16) sRPE-B and sRPE-L were 66 and 61 for matches, 51 and 49 for soccer, 86 and 67 for fitness, and 45 and 58 for resistance, respectively. Session RPE-B was rated most likely harder than sRPE-L for fitness (19 AU; 90% confidence limits: ±7) and most likely easier for resistance (-13; ±2). Match (5; ±4) and soccer (-3; ±2) differences were likely to most likely trivial. The within-player relationships between sRPE-B and sRPE-L were very likely moderate for matches (r = .44; 90% confidence limits: ±.12) and resistance training (.38; ±.06), likely large for fitness training (.51; ±.22), and most likely large for soccer training (.56; ±.03). Shared variance ranged from 14% to 35%. Conclusions: Practically meaningful differences between dRPE following physical training sessions coupled with low shared variance in all training types and matches suggest that sRPE-B and sRPE-L represent unique sensory inputs in girls` soccer players. The data provide evidence for the face and construct validity of dRPE as a measure of internal load in this population.